KUALITAS ARANG AKTIF DARI 5 JENIS KAYU (Activated charcoal quality from 5 wood species) - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Experimental study on several HTI wood species to produce activated charcoal is reported in this paper. The result showed that the yield of activated charcoal range from 30,35 - 43,25 %, moisture content from 9,23 - 13,34 %, ash content from 1,62 - 6,76 %, volatile matter from 4,94 - 6,65%, fixed carbon from 88,30- 91,73 %, adsorptive capacity of iodine from 1002 - 1130 mg/g and adsorptive capacity of benzene from 33,50 - 44,02 %. Based on adsorptive capacity of iodine, good quality of the activated charcoal was produce from sengon (Paraserienthes falcataria) wood species, this criteria has met the commercial standard requirement of the Indonesian Industrial Standard and Japanese Standard.The quality of the cajeput oil refined with the good quality of activated charcoal experiment shows that the cineol content became 23,17 % from,21,76 %.Key words : HTI timbers, Activated charcoal, Properties, Quality